Implementation of Merdeka Curriculum in Strengthening the Pancasila Profile of Elementary School Students - Yuwandra, Ari; Efendi, Nofriza (International Journal of Elementary School, 2025)
This study aims to reveal information, analyze and discuss the habituation carried out by students through the implementation of a Merdeka Curriculum in strengthening students' Pancasila profile values in the elements of faith, devotion to God Almighty, and noble character in grade IV in elementary schools. This research uses a qualitative approach with a descriptive type. Then the data were collected through observation, interviews, and documentation studies. Furthermore, data analysis went through three stages, namely data collection, data reduction, and data display. The subjects of this study were the principal, fourth grade teacher and fourth grade students. The results of data analysis by checking data from three different sources and analyzing the suitability of practices in the field concluded that the implementation of a Merdeka Curriculum in strengthening students' Pancasila profile is carried out through habituation which is grouped into routine habituation and spontaneous habituation and runs well. The habituation carried out is able to develop the character of religious and noble students in accordance with the main characteristics of the Pancasila student profile